P2X7 receptor antagonism increases regulatory T cells and reduces clinical and histological graft-versus-host disease in a humanised mouse model. Issue 3 (12th February 2021) - Cuthbertson, Peter; Geraghty, Nicholas J.; Adhikary, Sam R.; Casolin, Sienna; Watson, Debbie; Sluyter, Ronald
Abstract: Graft-versus-host disease (GVHD) is a severe inflammatory response arising from allogeneic haematopoietic stem cell transplantation. Previous studies revealed that antagonism of the P2X7 receptor with Brilliant Blue G (BBG) reduced liver GVHD but did not alter clinical GVHD in a humanised mouse model. Therefore, the present study aimed to trial a modified injection regime using more frequent dosing of BBG to improve outcomes in this model of GVHD. NOD- scid IL2Rγ null (NSG) mice were injected intraperitoneally (i.p.) with 10 × 10 6 human peripheral blood mononuclear cells (hPBMCs) (day 0), then daily with BBG (50 mg/kg) or saline (days 0–10). BBG significantly reduced clinical score, mortality and histological GVHD compared with saline treatment (endpoint). BBG significantly increased proportions of human regulatory T cells (Tregs) and human B cells and reduced serum human interferon-γ compared with saline treatment prior to development of clinical GVHD (day 21). To confirm the therapeutic benefit of P2X7 antagonism, NSG mice were injected i.p. with 10 × 10 6 hPBMCs (day 0), then daily with pyridoxalphosphate-6-azophenyl-2′, 4′-disulfonic acid (PPADS) (300 mg/kg) or saline (days 0–10). PPADS increased human Treg proportions compared with saline treatment (day 21), but potential clinical benefits were confounded by increased weight loss with this antagonist. To investigate the role of P2X7 antagonism on Treg survival, hPBMCs were cultured in reduced serum conditions to promote cell death. BBG increased proportions of Tregs (and B cells) compared with saline under these conditions. In conclusion, P2X7 antagonism reduces clinical and histological GVHD in a humanised mouse model corresponding to an increase in human Tregs.